Surface reactivity of tributyl thiophosphate: effects of temperature and mechanical stress - Rossi, A.; Piras, F.M.; Kim, D.; Gellman, A.J.; Spencer, N.D. (Tribology letters, 2006)
The surface reactivity of tributyl thiophosphate on iron surfaces has been studied in situ by attenuated total reflection Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy and temperature-programmed reaction and desorption spectroscopies. The results show that at temperatures lower than 373 K the molecule forms a physisorbed layer on the iron substrate. At 373 K a reaction takes place with the formation of an organic layer, together with iron polyphosphate and sulfate. At higher temperatures temperature-programmed desorption results suggest that the mechanism involves P–O bond scission to yield butoxy groups. This could be preceded by P=S bond scission to give tributyl phosphite, which then, in turn, undergoes P–O bond scission to produce butoxy groups. The results obtained following tribological testing are in agreement with those of thermal tests: evidence of polyphosphate and sulfate formation is found.